Study the effect of environmental noise on Infrared TX–RX Circuit Signals - Mohd Zaihan Ibrahim (Universiti Malaysia Perlis, 2008)
Infrared wireless communications systems have been massively growing in the past few years. There has been a high priority needs include systems for small group communications, portable receivers, and portable transmitters. However there are some limitations in infrared data transmission rate. In most of the indoor communication system environments, the receiver photodiode are exposed to ambient light which introduces optical noise to the receiver. This research discusses the environmental noise effecting infrared transmitter and receiver (TX-RX) circuit signal. Efforts on environmental noise reduction are also proposed. To improve the noise immunity against ambient light, the optical noises from the fluorescent lamp are analyzed and the behavior of an Amplitude Shift Keying (ASK) infrared communication link is modeled under these noises. Using an algorithm constructed, a digital demodulator is synthesized by employing Very High Speed Integrated Circuit Hardware Description Language (VHDL) in Altera Quartus II software, aiming at eliminating the subcarrier from optical noise. The simulation results obtained can proved that the used of this digital demodulator can achieve a noise immune data communication.